Experimental study on the flexural behavior of steel tube slab composite beams and key parameters optimization. Issue 11 (August 2019) - Jia, Pengjiao; Zhao, Wen; Guan, Yongping; Dong, Jiachao; Wang, Qinghe; Cheng, Cheng
This work presents an experimental study on the flexural behavior of steel tube slab composite beams subjected to pure bending. The main design elements considered in the work are the flange thickness, reinforcement ratio of high strength bolts, spacing between the tubes, and transverse patterns of the tube connections. Based on nine flexural experiments on simply supported steel tube slab specimens, the failure process and crack development in steel tube slab specimens, and their load–deflection curves are investigated. The results of the laboratory tests show that the welding of the bottom flange significantly improves the flexural capacity of the steel tube slab structure. In addition, a lower concrete's compressive strength improves the ductility of the steel tube slab specimens. Moreover, the flexural capacities predicted from the design guidelines are in good agreement with the experimental test results. Finally, based on the numerical simulations using the ABAQUS software, a numerical model is established to further investigate the effect of the additional parameters on the flexural capacity of steel tube slab structures. The numerical results suggested that the diameter of the steel bolts and the reinforcement ratio have a limited effect on the flexural bearing capacity of the steel tube slab beams, and the ultimate bearing capacity increases linearly along with increase in the diameter of the steel bolts and the reinforcement ratio in a certain range.